A Prescription for Wellness: Exercise Referrals at a Federally Qualified Health Center - Kelly R. Ylitalo; Wendy Cox; Mariela Gutierrez; Gabriel Benavidez; M. Renée Umstattd Meyer; Brock Niceler; Jackson O. Griggs (SAGE Publishing, 2020)
Introduction/Objectives: Physical activity (PA) improves quality of life and prevents chronic disease, but many adults are inactive. Planning with a health care provider in the form of an exercise "prescription" or referral may increase PA, but determinants of referral utilization are not well understood among underserved populations. This study examined sociodemographic and theory-based psychosocial determinants of exercise referral program utilization. Methods: Patients at a large, federally qualified health center with an on-site exercise facility (ie, "Wellness Center") referral were eligible to exercise with a personal fitness advisor. Self-reported PA behavior, self-efficacy, and self-regulation strategies were measured via survey and merged with electronic health records and attendance data. Negative binomial regression was used to estimate the rate of Wellness Center utilization. Results: Patients with exercise referrals (n = 1136) were, on average, 45.6 ± 14.6 years, 78.8% female, and 78.0% Hispanic/Latino or non-Hispanic Black. Approximately half (593/1136; 52.2%) initiated exercise at the Wellness Center; initiators completed 8.8 ± 12.4 visits during follow-up. Older age was associated with higher utilization ( P < .001) and patients meeting PA recommendations had lower utilization than patients not meeting recommendations (incident rate ratio = 0.72, 95% CI 0.53-0.97; P = .03). Baseline self-efficacy ( P < .001) and self-regulation strategies ( P = .03) were significantly associated with follow-up PA, even after adjusting for baseline PA. Conclusions: In this racially/ethnically diverse patient population, older and less active patients at baseline had higher program utilization. Patients with higher self-efficacy and self-regulation strategies reported higher PA over time. Community health centers have a unique opportunity to support PA through exercise referral programs to public health priority populations.